CAMBRIAN LINGULID AND ACROTRETID BRACHIOPODS FROM THE IGLESIENTE AREA (CAMPO PISANO FORMATION, SOUTHWESTERN SARDINIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Cambrian brachiopods from Sardinia are investigated for the first time in this paper. The silicified specimens come from nodular limestones of the late Early to Middle Cambrian Campo Pisano Formation of Gutturu Pala (southwestern Sardinia). The brachiopod fauna consists of lingulids and acrotretids and yields two new acrotretid species, described here as Opisthotreta sardica n.sp. and Vandalotreta proclinis n.sp. Material attributed to the genus Schmidtites is reported here for the first time from both the Middle Cambrian and western Gondwana. The genus Linnarssonella is reported for the first time from the Middle Cambrian and from outside North America. Whereas most brachiopods from Gutturu Pala biostratigraphically indicate a rather undifferenciated Middle Cambrian age, the last mentioned genus points to a late Middle Cambrian age for the uppermost part of the Campo Pisano Formation.